The evaluation of dual listing in borsaistanbul (BIST) and tehran stock exchange (TSE)in the context of gap analysis - GÜSAN KÖSE, GÖZDE; YÜKSEL, GÜL; ULUSAN POLAT, MELTEM; KELEMCİ, GÜLPINAR (My University, 2022)
Making difference in competition by efficient investments are mainly due to cost-effective resources. Relatively weak equity structures, high and volatile loan rates especially on behalf of the SMEs in Turkey, make it difficult to provide cost-effective funds.8 On the other hand, it is encouraged by the economy to open-up company’s’ shares to the public, as an alternative funding resource. Such public offering enables companies to be listed and traded at the stock exchange, as long as Listing Directive requirements are fulfilled.9 In case of listing shares of foreign corporations and listing shares of domestic corporations abroad, without public offering, is known as “dual listing”. BIST and TSE has signed Memorandum of Understanding (MoU) on the 26th of October, 2015. MoU has a vital importance for both countries, in terms of dual listing, considering the liquidity shortage and determining financial strategies around the world. Dual listing gives the opportunity to attract international investors to BIST. Furthermore, “capital market instruments, trading at main markets of foreign exchanges, determined by the Board of Directors, are able to be listed and traded at BIST without any requirement, following the confirmation of prospectus or certificate of issuance by the Capital Markets Board.” On the 29th of February, 2016, first Iran - Turkey Capital Markets Forum has been held and Turkish Committee, consisted of both financial sector and legal corporations’ representatives, has examined various cooperation alternatives. Besides information sharing, staff exchange and organizing common events; dual listing of existing or potential Islamic capital market instruments and derivatives, is determined as one of the most important focus area. Starting point of this study is providing scientific contribution in both negotiation and execution processes and strengthening the coordination and cooperation among the parties. Furthermore, it is targeted to provide added value to economy of knowledge, in order to increase the efficiency of dual listing for both countries. Hence, legal, financial, technological and socio-cultural infrastructures of both countries have been evaluated by GAP Analysis. GAP Analysis is a method used for measuring and comparing the potential and real condition and it avails to increase the performance, corporate effectiveness of a corporation or used for preparing strategic plan.14 By the support of GAP Analysis, comparisons in determined topics among Iran and Turkey have been made and concrete suggestions, due to present differences, have been given to all parties, in order to make arrangements, alignments and to formulate strategies.
Keywords: Dual Listing; Capital Markets; GAP Analysis.